KAJIAN LINGUISTIK FUNGSIONAL SISTEMIK PADA PEMBERITAAN KEKERASAN GENDER DALAM MEDIA CETAK LOMBOK POST DAN RELEVANSINYA TERHADAP PEMBELAJARAN WACANA DI PERGURUAN TINGGI - Irma Setiawan; Muhammad Sukri (Balai Bahasa Nusa Tenggara Barat, 2014)
Gender violence is a contemporary issue often discussed by the community in social interactions. In this case, the form of gender violence more easily found in the news media text with a variety of cases, such as: marriage, divorce, rape, molestation or sexual abuse, assault, robbery, sexual gratification or prostitution, and even murder motivated revenge romance. Therefore, the purpose of this study is to describe the representation of gender violence through transitivity system, modalities, and its relevance to discourse study in the university as well. The theory which is used in this study is the theory LFS presented by Halliday in which it focuses on the text , in this case the text of gender violence in the media. Data collection are performed by the method of literature analysis and note-taking. Sources of data obtained only on the text of gender violence in the media Lombok Post news. The collected data were analyzed by using both qualitative and quantitative method. The intended of those methods are to describe the research systematically, well organized, and patterned. The results of data analysis showed are domination of male’s action toward women in cases of domestic violence and non-domestic violence in the NTB area which had previously been analyzed through the system of transitivity and modality system. Women are more often represented as victims, whereas men often positioned as the doer in the act of gender violence, therefore the women are the aggrieved object in the cases of domestic violence and non-domestic violence.